RELASI GENDER DAN KEKUASAAN DALAM ISLAM INDONESIA - Yuberti, Yuberti (Universitas Islam Negeri Raden Intan Lampung, 2015)
THE GENDER RELATIONS AND POWERS OF ISLAM IN INDONESIA: This paper is a review of a book entitled Gender and Power in Indonesian Islam: Leaders, Feminists, Sufis and Pesantren Selves, edited by Bianca J. Smith and Mark Woodward published by Routledge, London and New York in 2014. This book examines the surrounding gender and development of the role of women in Indonesia, in terms of leadership, religious politics, feminism, mysticism and its influence in Indonesia, especially the world of boarding schools. This book is brave enough to revealed the theme about the issue of gender namely in pesantren. Like challenge the tiger in its cage. However, in contrast to gender studies written by Westerners in general, this book is certainly a protagonist and not hostile the Moslem such as the masterpiece of the Western people over the years. In addition, the book also involves some local writers. Most other Western writers submit data Indonesian Islamic studies in private in the sense of self- written. This is a new approach in the study of the contemporary orientalism which increases the load Islamic studies objectively. However, Islamic studies who stuck around women in this book still feel mono-paradigm though written by the East side (Indonesia) and the West side. Therefore, the gender paradigm is used to show the impression of partiality Islam against women at the same time which is practiced in the involvement of women on the political sphere leadership and Sufism in Lombok and Aceh which still depart from the paradigm of Western gender. In fact, the version of the typical domestic and gender approach demonstrated that women has the balance position with men and women can take the fight against the men domination as the echo from the western version idea about the gender.